A whole genome approach for discovering the genetic basis of blood group antigens: independent confirmation for P1 and Xga. Issue 3 (28th December 2018) - Lane, William J.; Aguad, Maria; Smeland‐Wagman, Robin; Vege, Sunitha; Mah, Helen H.; Joseph, Abigail; Blout, Carrie L.; Nguyen, Tiffany T.; Lebo, Matthew S.; Sidhu, Manpreet; Lomas‐Francis, Christine; Kaufman, Richard M.; et al.
Abstract : BACKGROUND: Although P1 and Xg a are known to be associated with the A4GALT and XG genes, respectively, the genetic basis of antigen expression has been elusive. Recent reports link both P1 and Xg a expression with nucleotide changes in the promotor regions and with antigen‐negative phenotypes due to disruption of transcription factor binding. STUDY DESIGN AND METHODS: Whole genome sequencing was performed on 113 individuals as part of the MedSeq Project with serologic RBC antigen typing for P1 (n = 77) and Xg a (n = 15). Genomic data were analyzed by two approaches, nucleotide frequency correlation and serologic correlation, to find A4GALT and XG changes associated with P1 and Xg a expression. RESULTS: For P1, the frequency approach identified 29 possible associated nucleotide changes, and the serologic approach revealed four among them correlating with the P1+/P1– phenotype: chr22:43, 115, 523_43, 115, 520AAAG/delAAAG (rs66781836); chr 22:43, 114, 551C/T (rs8138197); chr22:43, 114, 020 T/G (rs2143918); and chr22:43, 113, 793G/T (rs5751348). For Xg a, the frequency approach identified 82 possible associated nucleotide changes, and among these the serologic approach revealed one correlating with the Xg(a+)/Xg(a–) phenotype: chrX:2, 666, 384G/C (rs311103). CONCLUSION: A bioinformatics analysis pipeline was created to identify genetic changes responsible for RBC antigen expression. This study, in progress before the recently published reports, independently confirms the basis for P1 and Xg a . Although this enabled molecular typing of these antigens, the Y chromosome PAR1 region interfered with Xg a typing in males. This approach could be used to identify and confirm the genetic basis of antigens, potentially replacing the historical approach using family pedigrees as genomic sequencing becomes commonplace.